INVESTIGATING THE NETWORK TRAFFIC USING THE COMMAND-LINE PACKETS SNIFFER TCPDUMP IN KALI LINUX: INVESTIGATING THE NETWORK TRAFFIC USING THE COMMAND-LINE PACKETS SNIFFER TCPDUMP IN KALI LINUX - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this scientific article a comprehensive investigation of the network traffic using the command-line packets sniffer Tcpdump in kali Linux is made.